The Effect of Giving Complementary Therapy Baby Solus Per Aqua (Spa) on Motor Skills in Improving Growth and Development - Khairun Nisa, Hanik (Trigin Institute, 2024)
Infant growth and development are important aspects that are influenced by various factors, including environmental stimulation, nutrition, and physical therapy. One increasingly popular therapeutic approach is complementary therapy Baby Solus Per Aqua (Spa), which aims to improve infant motor skills through enjoyable stimulation and relaxation in water. This study aims to analyze the effect of Baby Spa therapy on infant motor skills. The method used in this study was an experimental test by taking samples of infants who received Baby Spa therapy regularly. The parameters measured included gross and fine motor development, such as arm and leg movements, head control, and responses to physical stimulation. The results showed that Baby Spa therapy contributed significantly to improving infant motor skills. Infants who received this therapy tended to have faster motor development than infants who did not receive similar therapy. In addition, warm water and massage techniques in spa sessions provide a relaxing effect that helps reduce muscle tension, thus supporting freer movement and better motor coordination. In conclusion, complementary therapy Baby Solus Per Aqua provides positive benefits for infant motor development, which ultimately also plays a role in improving overall growth and development. This therapy can be an alternative for parents to stimulate their baby's motor development in a safe and enjoyable way.